Prevalence of metabolic syndrome and associated factors in 11- to 17-year-old adolescents - Bortoloti, Durcelina Schiavoni; Pizzi, Juliana; Pavão, Fernando Henrique; Velasquez, Patricia Amaral Gurgel; Costa, Lediana Dalla; Fernandes, Rômulo Araujo; Cyrino, Edilson Serpeloni (Universidade Federal de Santa Catarina, 2015)
Abstract The adoption of health risk behaviors (low level of habitual physical activity and inadequate food and nutrient intake) has increased the prevalence of overweight/ obesity, particularly among adolescents. Thus, the prevalence of disorders and metabolic diseases has increased in this population. The aim of this study was to identify the prevalence of metabolic syndrome (MS) and to analyze its association with sport participation and overweight in adolescents aged 11 to 17 years. A total of 683 adolescents (301 boys and 382 girls) were randomly selected to compose the sample. The prevalence of MS was established based on fasting glucose, triglycerides, high-density lipoprotein (HDL-c), waist circumference, and blood pressure according to the cut-offs recommended by the Brazilian Society of Cardiology (2005). Nutritional status, sport participation, socioeconomic status, and alcohol consumption were analyzed as risk factors associated with MS. The presence of one or more risk factors was identified in 39.5% and 22.5% of the sample, respectively. The most prevalent MS components were low HDL-c (44.7%), high systolic blood pressure (32.4%), and elevated triglycerides (18.6%). The presence of MS was associated with both overweight and the lack of participation in sport ( P < 0.05). The results indicated an overall prevalence of MS of 5.4% in adolescent boys and girls. Furthermore, overweight and lack of sport participation were the main factors associated with MS.

Resumo A adoção de comportamentos de risco à saúde (reduzido nível de atividade física habitual, consumo inadequado de alimentos e nutrientes, entre outros) tem aumentado a prevalência de sobrepeso/obesidade, particularmente, em adolescentes. Assim, o número de disfunções e doenças metabólicas tem crescido nesta população. Portanto, o objetivo deste estudo foi identificar a prevalência de Síndrome Metabólica (SM) e analisar a sua associação com a prática esportiva e excesso de peso em adolescentes de 11 a 17 anos. Seiscentos e oitenta e três meninos (n = 301) e meninas (n = 382) foram selecionados aleatoriamente para comporem a amostra. A prevalência de SM foi estabelecida com base nos valores de glicose em jejum, triglicerídeos, lipoproteínas de alta densidade (HDL-c), circunferência de cintura e pressão arterial, de acordo com os pontos de corte recomendados pela Sociedade Brasileira de Cardiologia (2005). O estado nutricional, prática de esporte, nível socioeconômico e consumo de álcool foram analisados como fatores de risco associados a SM. A presença de um ou mais fatores de risco foi identificada em 39,5% e 22,5% da amostra, respectivamente. Os componentes da SM mais prevalentes foram HDL-c reduzida (44,7%), pressão arterial sistólica elevada (32,4%) e triglicérides elevado (18,6%). A presença de SM foi associada ao excesso de peso e a ausência da prática de esportes (P < 0,05). Os resultados indicaram uma prevalência total de SM na ordem de 5,4% em adolescentes de ambos os sexos. Adicionalmente, o excesso de peso e ausência da prática de esportes foram os principais fatores associados com a SM.
Prevalência de síndrome metabólica e fatores associados em adolescentes de 11 a 17 anos
Keywords: Adolescents; Metabolic syndrome; Obesity; Sports; Adolescentes; Esportes; Obesidade; Síndrome metabólica